The Influence of Teacher Performance on Learning Outcome of V-Graders - Suwartini, Sri; Rahmawati, Isna; Ferryka, Putri Zudhah (Journal for Lesson and Learning Studies, 2023)
Optimal learning conditions can be seen from the ability of teachers to manage students and teaching facilities in a pleasant atmosphere to achieve teaching goals, as well as to establish good interpersonal relationships between teachers and students and students with students. Based on, this  research aims to find out the influence of teacher performance on the learning outcomes of elementary school students. Population  of  this  study  amounted  to  45  people.  The  sample  of  this  study  was  23 people  who  were  determined  using  the  Randome  Sampling  technique learning achievement.    Data were collected through questionnaires and documentation to be then analyzed using descriptive statistics, normality test, linearity test, simple linear regression test, and coefficient of determination test. The results showed that teacher performance had an influence on the learning outcome of V SD N 1 Gentan students based on t-calculated > t-table (3.902 > 2.080) and the coefficient of determination of 0.20 showing that performance was able to explain the learning outcome of students by 42% while 58% was influenced by other variables.